PELAKOR AND YOUNG WIVES FROM A GENDER, LEGAL AND CULTURAL PERSPECTIVE: POWER DYNAMICS AND SOCIAL RELATIONS IN INDONESIAN HOUSEHOLDS - MUHAMMAD AHYAR; MURDAN; HALIMAH TUSAADIAH (LOIS: Jurnal Hukum dan Humaniora, 2025)
The phenomenon of homewreckers (pelakor) and young wives is a significant social issue in Indonesian domestic life. The term pelakor has emerged as a popular label reflecting emotional conflicts and power relations within the institution of marriage. Meanwhile, the presence of young wives, legitimized through polygamy, raises complex legal, social, and psychological problems. This article examines the phenomenon from gender, legal, and cultural perspectives, using feminism, Islamic family law, and popular culture as theoretical frameworks. Employing a qualitative literature-based method, the study reveals that the phenomenon of pelakor and young wives cannot be understood merely as personal conflicts but is deeply rooted in patriarchal structures, the legal legitimacy of polygamy, and cultural constructs that reproduce stigma. This research recommends reconstructing gender justice discourse, reformulating family law policies, and shifting social paradigms toward more equitable domestic relations.